Hubungan Kompetensi Guru Agama, dan Dukungan Orang Tua Terhadap Tingkat Religiusitas Remaja di SMA Unggulan Islam Kota Medan - Hilman Afif, Tansri Riziq; Nurmawati , Nurmawati; Al-Rasyid, Harun (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2025)
This study analyses the relationship between Islamic Education teachers' competence, parental support, and students' religiosity in two Islamic high schools in Medan City. The method used is quantitative with a correlational descriptive design. The sample consisted of 235 students, including 103 from Al-Azhar Medan High School and 132 from Plus As-Syafiyatul Amaliyah Medan High School, selected through stratified random sampling. Data was collected using a Likert scale questionnaire developed based on pedagogical and personality dimensions for teacher competence, House's social support theory for parental support, and Glock & Stark's five dimensions of religiosity. Instrument validity was tested through Pearson correlation and expert assessment, while reliability was measured using Cronbach's Alpha coefficient ≥ 0.60. Multiple linear regression analysis revealed that teacher competence did not significantly influence students' religiosity, while parental support had a significant positive influence. Simultaneously, both variables significantly influenced religiosity, contributing 35.8% to it. These findings confirm that the formation of students' religiosity does not solely depend on formal education but is also influenced by effective collaboration between schools and families. The results of this study support the developmental ecology theory, which emphasises the interaction of various systems in comprehensively shaping students' faith and moral values.